“Compreensão das propriedades estruturais e de superfície de catalisadores de platina promovidos com cério através de técnicas de caracterização in situ sob a reação de deslocamento gás-água” - Meira, Debora Motta (2014)
Pt based catalysts were measured with in situ X ray absorption fine structure spectroscopy (XAFS) to obtain information about the catalyst crystalline structure and electronic properties as a function of catalyst composition, method of preparation, inlet feed conditions and temperature. In these experiments, two type of catalysts were studied: i) nanoparticles of Pt occluded in Al2O3 or CeO2-Al2O3 matrix containing 1.5 % of Pt where two different methods to incorporate the cerium were used and ii) conventional Pt supported catalysts containing 0.3 and 1 % of Pt on Al2O3 or with addition of 6 or 12 % of ceria. For catalysts based on nanoparticles, XAFS spectra were acquired at Pt L3-edge and Ce K and L3-edge under reduction and water gas shift (WGS) reaction conditions. The XAFS results reveal, after the reduction, the presence of Pt nanoparticles with similar coordination numbers (NPt-Pt), about 6, and similar Pt-Pt distances, about 2.75  0.01 Å. The catalyst activity for WGS and the strength of interaction between the metal and the support are related with cerium oxide structure revealed by XAFS analysis at Ce K and L3 edges. In situ infrared spectroscopy under WGS conditions revealed the presence of formates on the catalyst surface and that they are probably spectators for the reaction. It was possible to observe that these catalysts changes according to the atmosphere and temperature. Thus, it was possible to demonstrate, using the pre-formed nanoparticles that several parameters affect the catalyst behavior like: the metallic and the oxide particle size, the contact between them and what is exposed on the surface. For the conventional catalysts, the addition of ceria on 03PtAl sample enhances Pt oxidation, reflecting in a larger Pt-O coordination number for this sample. After reduction, 03PtAl resulted in larger Pt particles compared to the 12Ce03PtAl. For Ce-containing samples, in addition to the Pt-Pt contribution, a Pt-O contribution had to be considered to fit the spectra. This Pt-O increases proportionally to the cerium amount demonstrating that Pt clusters are anchored on support through a Pt-O bond. The Pt structure changes depends on the temperature, support nature and reactants composition, demonstrating that the catalytic properties requires the use of in situ characterization techniques.